Implementación de un plan de mantenimiento preventivo del sistema hidráulico a la compactadora MCNEILUS en Interaseo Santa Marta (2020)
This article focused on keeping the equipment operable in perfect working order and reducing costs in the maintenance of the hydraulic system of the MCNEILUS compactor in Santa Marta. Preventive maintenance was and is of vital importance in the conservation and prolongation of the useful life of the different machinery, which began to be taken into account after the industrial revolution, through the year’s maintenance has evolved and today by today we can talk about preventive, corrective, predictive maintenance, among others. The main objective of this research is to meet the proposed goal of detecting possible shortcomings in the machinery of the hydraulic system of the MCNEILUS compactor in INTERASEO Santa Marta and to create reliability by operators and equipment in optimal conditions.